Arsenic Content in Smokeless Tobacco Products Consumed by the Population of Pakistan: Related Health Risk. (27th November 2019) - Arain, Sadaf Sadia; Kazi, Tasneem Gul; Afridi, Hassan Imran; Brahman, Kapil Dev; Naeemullah,; Shah, Faheem; Mughal, Moina Akhtar
Abstract: Extensive investigation has shown that smokeless tobacco (SLT) may cause inflammation of the oral cavity. In this study, the concentration of arsenic (As) was determined in SLT products (gutkha, mainpuri, and dry and moist snuff). Scalp hair samples of males aged 20–30 years who consumed different types of SLT products available in Pakistan were analyzed for As contents. Total As in different SLT products and in scalp hair was determined by electrothermal atomic absorption spectrometry after microwave-assisted extraction. The validity of the methodology was tested by simultaneously analyzing certified reference materials and spike recovery studies. The range of As concentrations in moist snuff, dry snuff, gutkha, and mainpuri were 0.574–1.53, 0.642–1.07, 0.246–0.622, and 0.419–0.874 μg/g, respectively. We estimated that a daily intake of 10 g of all SLT products could contribute 2.0–12.2% of the provisional maximum tolerable daily intake for As in adults. The As concentration in scalp hair of SLT consumers was higher than that of referents who had not consumed any type of tobacco products.